The Realization and Limitations of “Filial Piety Ethics” in Robotic Caregiving - Sun, Anyang; Li, Haoyu (International journal of technoethics, 2025)
The three levels of “shallow care,” “deep care,” and “good care” in robotic caregiving largely correspond to the concepts of “supporting parents,” “pleasing parents,” and “respecting parents” in traditional Chinese filial piety ethics, enabling the application of caregiving robots within the context of Chinese filial culture. However, in the practical application of caregiving robots, there are issues such as ambiguity in defining the moral responsibility of the caregiving subject, the illusory nature of the emotional relationship between humans and robots, objectification of the elderly, and challenges faced by traditional Chinese parent-child relationships. Therefore, the role of caregiving robots should be carefully evaluated. They should not be seen as replacements for children but as tools to assist children in fulfilling their filial duties when caring for elderly parents.